PENGARUH PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI - Wahyuningsih, Endah Tri; Santa, Santa; Suchyadi, Yudhie (Universitas Pakuan, 2021)
THE EFFECT OF VOCABULARY MASTERY ON ESSAY WRITING SKILLS DESCRIPTIONThe purpose of this study was to determine the effect of vocabulary mastery on description essay writing skills. The method used is a quantitative method with a causal technique. The data of this study were obtained by using multiple choice tests for vocabulary mastery variables and description tests for variable description writing skills. The population in this study were students of grade IV 03 Karangtengah State Elementary School, Babakanmadang, Bogor Regency, totaling 66 students. The sample used was 40 students, obtained by calculation using the Taro Yamane formula. Simple regression analysis and correlation techniques produce a relationship model that is expressed in the form of a regression equation that is Å¶ = (49 + 0.4X), with a price of 38.808 greater than the real level of 0.05 at 4.01 and contributions based on research results of 90%. Based on the results of these studies, it can be concluded that there is a positive and significant influence between vocabulary mastery of the writing essay skills in students.